Serologic evidence of human influenza virus infections in swine populations, Cambodia. Issue 3 (30th May 2012) - Rith, Sareth; Netrabukkana, Punnaporn; Sorn, San; Mumford, Elizabeth; Mey, Channa; Holl, Davun; Goutard, Flavie; Y, Bunthin; Fenwick, Stan; Robertson, Ian; Roger, François; Buchy, Philippe
<x xml:space="preserve">Abstract</x> Background This study was conducted from 2006 to 2010 and investigated the seroprevalence of influenza A viruses in Cambodian pigs, including human H1N1, H3N2, 2009 pandemic H1N1 (A(H1N1)pdm09), and highly pathogenic avian H5N1 influenza A viruses. Methods A total of 1147 sera obtained from pigs in Cambodia were tested by haemagglutination inhibition (HI) assays for antibody to human influenza A viruses along with both HI and microneutralization (MN) tests to assess immunological responses to H5N1 virus. The results were compared by year, age, and province. Results Antibodies against a human influenza A virus were detected in 14·9% of samples. A(H1N1)pdm09 virus were dominant over the study period (23·1%), followed by those to human H1N1 (17·3%) and H3N2 subtypes (9·9%). No pigs were serologically positive for avian H5 influenza viruses. The seroprevalence of human H1N1 and H3N2 influenza viruses peaked in 2008, while that of A(H1N1)pdm09 reached a peak in 2010. No significant differences in seroprevalence to human influenza subtypes were observed in different age groups. Conclusions Cambodian pigs were exposed to human strains of influenza A viruses either prior to or during this study. The implications of these high prevalence rates imply human‐to‐swine influenza virus transmission in Cambodia. Although pigs are mostly raised in small non‐commercial farms, our preliminary results provide evidence of sustained human influenza virus circulation in pig populations in Cambodia.